A novel approach to needs assessment in curriculum development: Going beyond consensus methods. (May 2014) - Gonsalves, Carol L.; Ajjawi, Rola; Rodger, Marc; Varpio, Lara
Abstract Background: Needs assessment should be the starting point for curriculum development. In medical education, expert opinion and consensus methods are commonly employed. Aim: This paper showcases a more practice-grounded needs assessment approach. Methods: A mixed-methods approach, incorporating a national survey, practice audit, and expert consensus, was developed and piloted in thrombosis medicine; Phase 1: National survey of practicing consultants, Phase 2: Practice audit of consult service at a large academic centre and Phase 3: Focus group and modified Delphi techniques vetting Phase 1 and 2 findings. Results: Phase 1 provided information on active curricula, training and practice patterns of consultants, and volume and variety of thrombosis consults. Phase 2's practice audit provided empirical data on the characteristics of thrombosis consults and their associated learning issues. Phase 3 generated consensus on a final curricular topic list and explored issues regarding curriculum delivery and accreditation. Conclusions: This approach offered a means of validating expert and consensus derived curricular content by incorporating a novel practice audit. By using this approach we were able to identify gaps in training programs and barriers to curriculum development. This approach to curriculum development can be applied to other postgraduate programs.